Galectin-3 levels are associated with right ventricular functional and morphologic changes in pulmonary arterial hypertension - Fenster, Brett E.; Lasalvia, Luis; Schroeder, Joyce D.; Smyser, Jamey; Silveira, Lori J.; Buckner, J. Kern; Brown, Kevin K. (Heart and vessels, 2016)
The response of the right ventricle (RV) to pulmonary arterial hypertension (PAH) involves changes in contractile function, chamber size, hypertrophy, and extracellular matrix (ECM). Galectin-3 (Gal-3) is a mediator of myocardial ECM metabolism and biomarker for left heart remodeling, yet its ability to reflect RV remodeling is unknown. We hypothesized that serum Gal-3 levels correlate with RV morphology and function in PAH, and that Gal-3 is associated with circulating markers of ECM. Fifteen subjects with PAH and 10 age-matched controls underwent same-day echocardiography, cardiac magnetic resonance (CMR) imaging, and phlebotomy for Gal-3 and ECM biomarkers including N-terminal propeptide of type III collagen type (PIIINP), tissue inhibitor of metalloproteinase-1 (TIMP-1), and hyaluronic acid (HA). RV ejection fraction, end diastolic volume index, end systolic volume index, and mass index were calculated using CMR. Echocardiography was used to estimate RV systolic pressure and measure RV strain. Serum Gal-3, TIMP-1, and HA levels were all significantly increased in PAH subjects when compared to controls. Gal-3 correlated with RV ejection fraction ( ρ −0.44, p 0.03), end diastolic volume index ( ρ 0.42, p 0.03), end systolic volume index ( ρ 0.44, p 0.027), mass index ( ρ 0.47, p 0.016), systolic pressure ( ρ 0.55, p < 0.001), and strain ( ρ 0.43, p 0.03). Gal-3 levels positively correlated with the ECM markers TIMP-1 and HA but not with PIIINP. In conclusion, Gal-3 levels are associated with multiple indices of RV function and morphology. Gal-3 may represent a novel biomarker for RV remodeling and associated ECM turnover in PAH.